2018
DOI: 10.1007/s12010-018-2858-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma ALU-247, ALU-115, and cfDNA Integrity as Diagnostic and Prognostic Biomarkers for Breast Cancer

Abstract: Diagnosis of breast cancer (BC) by using sensitive and specific biomarkers is necessary. Cell-free DNA is a candidate biomarker in various cancers. Contrasting, shorted uniformed DNA released from apoptotic non-diseased cells, DNA released from malignant cells varies in size. DNA integrity is a ratio between 247 and 115 bp. So, this study was designed to investigate the role of plasma ALU-247, ALU-115, and DNA integrity as possible diagnostic and prognostic markers in BC patients as compared to plasma CA15.3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…In CRC samples, the cfDNA integrity index determined using the biocomposite platform was lower (0.18) than that obtained using the conventional method (0.27). This result confirmed that the biocomposite platform easily captured the small DNA fragments, which can be regarded as reliable evidence of the whole tumor burden 38 . The cellular DNA background using the biocomposite platform, the DNAs were amplified with the β-actin 400 bp primer.…”
Section: Synthesis and Optimisation Of Biocomposites A Protocol For supporting
confidence: 75%
“…In CRC samples, the cfDNA integrity index determined using the biocomposite platform was lower (0.18) than that obtained using the conventional method (0.27). This result confirmed that the biocomposite platform easily captured the small DNA fragments, which can be regarded as reliable evidence of the whole tumor burden 38 . The cellular DNA background using the biocomposite platform, the DNAs were amplified with the β-actin 400 bp primer.…”
Section: Synthesis and Optimisation Of Biocomposites A Protocol For supporting
confidence: 75%
“…In most clinical studies, cfDNA was suggested to be a promising diagnostic indicator . In addition, several reports on different cancers ascribed a prognostic value of cfDNA measurements to disease‐free or overall survival .…”
Section: Discussionmentioning
confidence: 99%
“…16 In most clinical studies, cfDNA was suggested to be a promising diagnostic indicator. 6,17,18 In addition, several reports on different cancers ascribed a prognostic value of cfDNA measurements to disease-free or overall survival. 19,20 However, data on the prediction and monitoring of therapy response in cancer patients undergoing NCT are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma ALU-247, ALU-115, and DNA integrity may be proven to have clinical utility in BC diagnosis. 64 In metastatic settings, Cheng et al showed a significantly increased cfDI (P = 1.21E-7 for ALU and P = 1.87E-3 for LINE1) in both Figure 1 The whole process of ctDNA analysis and possible influencing factors. Notes: The concentration of ctDNA and mutation frequency are significantly higher in ABC than early BC.…”
Section: The Cutoff Of Ctdna Concentrationmentioning
confidence: 97%